Crack initiation and fracture features of Fe–Co–B–Si–Nb bulk metallic glass during compression - S. Lesz; A. Januszka; S. Griner; R. Nowosielski (Fracture and Structural Integrity)
The aim of the paper was investigation crack initiation and fracture features developed during compression of Fe-based bulk metallic glass (BMG). These Fe-based BMG has received great attention as a new class of structural material due to an excellent properties (e.g. high strength and high elasticity) and low costs. However, the poor ductility and brittle fracture exhibited in BMGs limit their structural application. At room temperature, BMGs fails catastrophically without appreciable plastic deformation under tension and only very limited plastic deformation is observed under compression or bending. Hence a well understanding of the crack initiation and fracture morphology of Fe-based BMGs after compression is of much importance for designing high performance BMGs. The raw materials used in this experiment for the production of BMGs were pure Fe, Co, Nb metals and nonmetallic elements: Si, B. The Fe–Co–B–Si–Nb alloy was cast as rods with three different diameters. The structure of the investigated BMGs rod is amorphous. The measurement of mechanical properties (Young modulus - E, compressive stress - ?c, elastic strain - ?, unitary elastic strain energy – Uu) were made in compression test. Compression test indicates the rods of Fe-based alloy to exhibit high mechanical strength. The development of crack initiation and fracture morphology after compression of Fe-based BMG were examined with scanning electron microscope (SEM). Fracture morphology of rods has been different on the cross section. Two characteristic features of the compressive fracture morphologies of BMGs were observed. One is the smooth region. Another typical feature of the compressive fracture morphology of BMGs is the vein pattern. The veins on the compressive fracture surface have an obvious direction as result of initial displace of sample along shear bands. This direction follows the direction of the displacement of a material. The formation of veins on the compressive fracture surface is closely related to the shear fracture mechanism. The results of these studies may improve the understanding on the fracture features and mechanisms of BMGs and may provide instructions on future design for ductile BMGs with high resistance for fracture.